Tratamento enzimático e antimicrobiano em filmes de amido e gelatina recuperada de resíduos de couro curtido ao cromo III - Rosseto, Marieli (2020)
The reuse of agro-industrial waste for the production of biodegradable films is considered a sustainable alternative to replace polymers of fossil origin. Among the potential sources for its elaboration, the combination of proteins and polysaccharides stands out for improving the stability of the polymer matrix. However, the challenge in replacing traditional synthetic polymers with materials from renewable sources is structural and functional stability during storage and use. To achieve this objective, it is necessary to study alternatives that allow to prolong the useful life of these polymers, making their applicability feasible. In this context, this study aims to improve the properties of corn starch and gelatin films recovered from leather residues tanned to chromium III (RCCC), through the addition of transglutaminase enzyme (TGase) and phenolic extracts of Spirulina platensis. To evaluate the performance of RCCC gelatine on the properties of the films, its performance was compared with commercial gelatine. The influence of the addition of enzyme and Spirulina phenolic extract on the films was verified by determining the mechanical, thermal, chemical, physical and biological properties of the films. Subsequently, the films were exposed to three different accelerated aging processes that allow the simulation of possible applications: thermo-oxidation (TO) (70 ° C), ultraviolet radiation (UV) (40 w solar lamps, at 30 ± 1 ° C) and humidity (UR) (75% humidity at 30 ° C), for 64 hours, for further characterization. At the end, the degradation of the films in soil on the surface was evaluated (during 60 days - to evaluate the possibility of applying the film as soil cover), and between soil layers (64 hours - evaluating how the film would behave for degradation after application). Among the elaborated films, all presented malleability, uniform coloring, without breaks or brittle areas. The results show that the use of additives showed efficiency for the films made with RCCC gelatin, improving its properties and bringing them closer to the control films, made with commercial gelatin, they did not obtain the same performance with the use of additives, being that the addition of Spirulina phenolics made them more permeable and soluble. While the RCCC films showed significant improvements for the use of both additives, enzyme and the Spirulina phenolic extract, the former decreased water solubility (53%) and water vapor permeability (2.49%), and the second acted by reducing solubility (17.35%), Aw (1.25%), permeability (15.48%) and thickness (9.09%). Also, both the enzyme and phenolic extract Spirulina exhibited good antimicrobial properties for Aspergillus niger (RCCC: 8.54%; 40.30%) and Bacillus pumilus (RCCC: 9.98%; 45.48%), respectively. Evaluating soil degradation, films with Spirulina and with enzyme in its composition took longer to degrade physically, which makes them meet the demand for a longer useful life, and can be applied in an environment that monitors humidity and UV light, such as soil cover inside greenhouses, in the planting of vegetables, such as lettuce and arugula, which have a short cycle between planting and harvesting. And at the end of the process, when they are discarded, they return to the cycle in the form of organic matter, helping in the development of plants, contributing to environmental sustainability.